Links between taxes and economic growth :Some empirical evidence - Marsden, Keith (Washington, 1983)
Evidence from 20 countries shows that those with lower taxes experienced more rapid expansion of investment, productivity, employment, and government services, and had better growth rates--without discriminat ing against the poor. This paper examines the mechanisms by which fiscal policies may have affected their performance.
Keywords: Taxation case studies